Evaluating the effect of two-dimensional molecular layout on DNA origami-based transporters. Issue 9 (19th April 2023) - Fukumoto, Kodai; Miyazono, Yuya; Ueda, Takuya; Harada, Yoshie; Tadakuma, Hisashi
Abstract : Single-molecule fluorescence imaging of DNA origami-based transporters showed shorter run lengths in dence layouts of kinesin motors. Abstract : Cellular transport systems are sophisticated and efficient. Hence, one of the ultimate goals of nanotechnology is to design artificial transport systems rationally. However, the design principle has been elusive, because how motor layout affects motile activity has not been established, partially owing to the difficulty in achieving a precise layout of the motile elements. Here, we employed a DNA origami platform to evaluate the two-dimensional (2D) layout effect of kinesin motor proteins on transporter motility. We succeeded in accelerating the integration speed of the protein of interest (POI) to the DNA origami transporter by up to 700 times by introducing a positively charged poly-lysine tag (Lys-tag) into the POI (kinesin motor protein). This Lys-tag approach allowed us to construct and purify a transporter with high motor density, allowing a precise evaluation on the 2D layout effect. Our single-molecule imaging showed that the densely packed layout of kinesin decreased the run length of the transporter, although its velocity was moderately affected. These results indicate that steric hindrance is a critical parameter to be considered in the design of transport systems.